Molecular Characterization And Production Of A Specific Recombinant Protein Of Shigella Flexneri: Towards Development Of A Rapid Immunochromatography Diagnostic Test For Dysentery - Kirnpal , Kaur Banga Singh (2006)

(untitled)
Disenteri basil us atau juga dikenali sebagai shigelosis disebabkan terutamanya oleh bakteria Shigella. Shigelosis merupakan suatu penyakit yang serius di mana hampir 165 juta penduduk dijangkiti setiap tahun. la merupakan infeksi enterik invasif yang biasanya mempunyai gejala seperti demam, sakit abdomen dan diarea berdarah. S. fJexneri merupakan spesies yang paling kerap dipencilkan dan biasanya menyebabkan shigelosis secara endemik di negara yang sedang membangun. Kaedah pengesanan rutin bergantung kepada teknik pengkulturan dan pengenalpastian Shigella spp. daripada tinja, adalah sukar dan memerlukan proses ujikaji yang cerewet, memakan masa 3 hingga 5 hari dan mempunyai sensitiviti yang rendah. Bacillary dysentery is caused mainly by infection with Shigella spp. which is also known as shigellosis. It remains a common and serious health problem throughout the world and has been estimated to infect about 165 million people worldwide annually. It is an acute invasive enteric infection often characterized by abdominal pain, fever and bloody diarrhea. S. flexneri is the most frequently isolated species causing endemic shigellosis in developing countries. The current method of diagnosis still depends on the traditional culture method, which is laborious, relatively insensitive and takes 3 to 5 days to produce result.